Monetary Theory of the Genesis of the State, Prospects for Electronic Money and Transnational Law - Sarsembayev, Daniyar (International Journal of Criminology and Sociology, 2021)
This article is an attempt to explain a new way of the cause of the emergence of the state with simultaneous consideration of previously known theories in legal science. Several arguments are presented in favor of the new theory, which, in the author’s opinion, are sufficiently valid. The author analyzes the dynamics of the development of the causes of the emergence of state and law and its influence on the transformation of the latest civilizations, which took place in history. Based on the historical chronology of the emergence and functioning of money, the author conventionally differs three stages in its development: 1) the period of the gold standard or a chronic shortage of monetary liquidity; 2) the period of paper money and inflationary pressure; 3) the digital money period. The author upholds a new position regarding the essence of international law, believing that international law is not a separate system of law, but only the result of the evolution of law from national to international, which became possible thanks to the development of the institution of money. The author shares his thoughts on the true reason for justifying the state’s right to war in international law a while back, expressed in a persistent shortage of monetary liquidity, which took place from the moment the first civilizations appeared until the 20th century. This article establishes a projection for the further development of state and law, including international law, alongside the inevitable transition of the world community to the digital money supply. The article reveals not only the vision of the new monetary system, its absolute transparency, and clarity but also the various opportunities we face in such a transition. In this regard, the states and the world community will come to clear and effective outcomes in management, to the practical abolition of corruption and economic crime, to legal methods of conducting all competitions and public procurement, to fair and effective justice, and the establishment of highly moral relations in society.